MYASTHENIA GRAVIS - Dewi Permata Sari; Shahdevi Nandar Kurniawan (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2023)
Myasthenia gravis is an autoimmune disease of the postsynaptic membrane, especially acetylcholine receptors in the neuromuscular link of skeletal muscle. Patients with myasthenia gravis have a high number globally. The disease occurs due to a disorder that impairs the impulse connection between chemicals traveling from nerve endings and receptors. Clinical symptoms include weakness of the eye muscles (ptosis and diplopia), difficulty swallowing, and difficulty speaking. The diagnosis of myasthenia gravis is based on the patient's complaints obtained in the history, physical and neurological examination, and supporting examinations. The management that can be given is intravenous immunoglobulin (IVIg) therapy, plasma exchange (PE), corticosteroids given together with IVIg and PE, or acetylcholinesterase inhibitors. These treatments can determine the patient's prognosis. If the patient with myasthenia gravis is left to involve the respiratory muscles, then the patient's prognosis becomes worse. In addition, myasthenic crisis and cholinergic crisis may occur, which is a medical emergency.